Human Papilloma Viruses and Breast Cancer - Lawson, James S.; Glenn, Wendy K.; Salyakina, Daria; Delprado, Warick; Clay, Rosemary; Antonsson, Annika; Heng, Benjamin; Miyauchi, Shingo; Tran, Dinh D.; Ngan, Christopher C.; Lutze-Mann, Louise; Whitaker, Noel J. (Frontiers in Oncology, 2015)
Purpose: Human papillomaviruses (HPV) may have a role in some breast cancers. The purpose of this study is to fill important gaps in the evidence. These gaps are: (i) confirmation of the presence of high risk for cancer HPVs in breast cancers, (ii) evidence of HPV infections in benign breast tissues prior to the development of HPV positive breast cancer in the same patients, (iii) evidence that HPVs are biologically active and not harmless passengers in breast cancer. Methods: RNA-seq data from The Cancer Genome Atlas (TCGA) was used to identify HPV RNA sequences in breast cancers. We also conducted a retrospective cohort study based on polymerase chain reaction (PCR) analyses to identify HPVs in archival specimens from Australian women with benign breast biopsies who later developed breast cancer. To assess whether HPVs in breast cancer were biologically active, the expression of the oncogenic protein HPV E7 was assessed by immunohistochemistry (IHC). Results: Thirty (3.5%) low risk and 20 (2.3%) high risk HPV types were identified in 855 breast cancers from the TCGA data base. The high risk types were HPV 18 (48%), HPV 113 (24%), HPV 16 (10%), HPV 52 (10%). Data from the PCR cohort study, indicated that HPV type 18 was the most common type identified in breast cancer specimens (55% of 40 breast cancer specimens) followed by HPV 16 (13%). The same HPV type was identified in both the benign and subsequent breast cancer in 15 patients. HPV E7 proteins were identified in 72% of benign breast specimens and 59% of invasive breast cancer specimens. Conclusions: There were 4 observations of particular interest: (i) confirmation by both NGS and PCR of the presence of high risk HPV gene sequences in breast cancers, (ii) a correlation between high risk HPV in benign breast specimens and subsequent HPV positive breast cancer in the same patient, (iii) HPVs in breast cancer are likely to be biologically active (as shown by transcription of HPV DNA to RNA plus the expression of HPV E7 proteins), (iv) HPV oncogenic influences may occur early in the development of breast cancer.